Centrosema (Centrosema pubescens) Leaf Meal as Protein Supplement for Pullet Chicks and Growing Pullets - Nworgu, F.C.; Fasogbon, F.O. (International Journal of Poultry Science, 2007)
The study was conducted to determine the optimum dietary inclusion rate of Cetrosema pubescens leaf meal (CLM) for pullet chicks (PC) and growing pullets (GP). Eighty four Black Nera pullet chicks were weighed and randomly allotted to four dietary treatments which contained 0, 2, 4 and 6% CLM for A, B, C and D, respectively in a completely randomized design. Treatment A served as control and each treatment was replicated 3 times. The PC experiment lasted for 6 weeks, while the GP experiment lated for 8 weeks i.e after 4 weeks of acclimatization after chicks experiment. The results revealed that inclusion of 2-6% CLM for PC did not have significant (P>0.05) effect on the mean body weight gain (MBWG), feed conversion ratio (FCR), protein efficiency ratio (PER) unlike feed and water intake. However, MBWG, FCR, PER and cost of feed per kilogram live weight gain (CFPKLING), for the GP were significantly (P<0.05) influenced by the dietary inclusion of 2-6%CLM over control. Dietary inclusion of 2-6% CLM for the PC reduced the MBWG averagely by 31.82% over the control, while its inclusion for the GP increased MBWG averagely by 4.61% with reference to control. The decreased in the MBWG for the PC was significance and progressive with the increased concentrations of CLM. Inclusion of 2-6% CLM for PC increased CFPKLWG by 34.38% over control, while for the GP, this parameter was reduced by 12.29% averagely. Hence it is not advisable to include 2-6% CLM in the diet of PC, while 2% CLM is recommended for the GP.